Day 2 Wed, March 27, 2019 2019
DOI: 10.2523/iptc-19315-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development and Remaining Challenges of Iron Sulfide Scale Mitigation in Sour Gas Wells

Abstract: Iron sulfide scale deposition can be a significant flow assurance issue in the sour gas production systems. It can deposit along the water flowing path from near wellbore reservoir area to surface equipment, which results in formation damage, causes tubing blockage, interferes with well intervention, and reduces hydrocarbon production. The main objectives of this paper are to review on the new advancements and remaining challenges of iron sulfide scale management in sour gas wells, covering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition to that formulation, new copolymer chemistry containing the acrylamide, phosphonic acid, and sulfonic acid acrylic units has successfully prevented FeS formation when injected as 0.75 ppm active polymer . Importantly, it is suggested that inhibitors based on dispersion mechanism are more convenient to be employed for FeS inhibition cases in typical sour gas wells rather than nucleation and crystal-growth-based inhibitors …”
Section: Field Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to that formulation, new copolymer chemistry containing the acrylamide, phosphonic acid, and sulfonic acid acrylic units has successfully prevented FeS formation when injected as 0.75 ppm active polymer . Importantly, it is suggested that inhibitors based on dispersion mechanism are more convenient to be employed for FeS inhibition cases in typical sour gas wells rather than nucleation and crystal-growth-based inhibitors …”
Section: Field Case Studiesmentioning
confidence: 99%
“…Another nonchemical corrosion prevention technique is the antiscalants coating with stable materials withstanding the harsh downhole conditions in sour gas wells. 70 The antiscalants are adsorbed onto the fluid boundary layer, thus eliminating the scales deposition onto the metal surfaces. Several types of protective coatings are applied on the inner surfaces of oil and gas transmission pipelines.…”
Section: Iron Sulfide Scale Inhibition and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that there was a limited effect on the dissolution rate by increasing volume ratio of the dissolver with the scale mass and increasing agitation under the test conditions [39]. Recent studies were performed to find an effective chemical solution for removing the precipitated iron sulfide scales, and improving the scale dissolution [40][41][42].…”
Section: Iron Sulfide Scale Removalmentioning
confidence: 99%
“… 1 It is reported that scales can deposit in many forms and in different locations in the well; for example, iron sulfide can deposit near the wellbore region, downhole, and topside tubes of the well, in addition to the sides of the reservoir. 2 Different wells may have scales that are different in composition, severity, and depth. For example, at around 2 km on the downhole tubing, the scale starts to be noticeable, and the severity increases with the depth.…”
Section: Introductionmentioning
confidence: 99%